The The Suitability of Post-Method Pedagogy for Merdeka Curriculum - Razaq, Siti Ulfya Syahara Razaq (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
This research intends to analyse Post-Method Pedagogy in Merdeka curriculum. The major reflecting of this research is to criticise available Post-Method Pedagogy as one of approaches to pedagogical methodology in English Learning Teaching (ELT). The methodology used is qualitative research through literature study. To collect the data, the researcher peels literary references from journals which closely relate with the issue being discussed. The primary outcome of research is as follows. To understand post-method pedagogy, Merdeka curriculum and suitability post-method pedagogy used in Merdeka curriculum. Then, the expected result may be a consideration for teachers as practitioners, educational policy makers to adjust this approach in implementing pedagogical practice in English Learning Teaching (ELT) to achieve an education’s goals.